Jurnal Kata: an interdisciplinary study of narrative structure in dash akol as a short story and dash akol as a movie - Dashti, azam, Hadidi, yaser (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
this paper undertakes an interdisciplinary study of the short story dash akol and the movie adapted from it.